ANDRAGOGIC STRATEGIES FOR GRADUATE STUDENTS FROM TECHNOLOGICAL MEDIATION PROCESS - Veytia Bucheli, María Guadalupe (Atenas, 2015)
The paper discusses the importance of using andragogic strategies for graduate students from processes of technological mediation. The characteristics of the Society of the XXI Century are described, conceptualization and assumptions of andragogy as key to the development of teaching processes pillars - oriented adult learning; and some andragogic strategies mediated by technology from synchronous and asynchronous communication processes that facilitate and enrich the collaborative construction of knowledge by students are described. Finally the conclusions that were reached after performing this research are presented.